Inequality, Transfers and Growth : New Evidence From the Economic Transition in Poland - Prasad, Eswar; Keane, Michael (Washington, D.C. : International Monetary Fund, 2000)
This paper challenges the conventional wisdom that inequality in Poland increased markedly during the economic transition. Income and consumption inequality actually declined in 1990-92 and rose only moderately above pre-transition levels by 1997. However, inequality in labor earnings increased markedly and consistently during 1990-97. Social transfer mechanisms, including pensions, helped mitigate increases in overall inequality and poverty. More importantly, these transfer mechanisms were well-designed to reduce political resistance to market-oriented reforms in the early years of transition, paving the way for rapid growth. Cross-country evidence from transition economies is consistent with this interpretation and with recent literature suggesting that inequality-reducing redistribution can enhance growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet